2020
DOI: 10.1186/s12891-020-03517-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of scoliosis-specific exercises for alleviating adolescent idiopathic scoliosis: a systematic review

Abstract: Background: Adolescent idiopathic scoliosis (AIS) is the most common pediatric spinal deformity with reported complications including pain, mental health concern and respiratory dysfunction. The scoliosis-specific exercise (SSE) is prescribed throughout pubertal growth to slow progression although effects are unclear. This review aims to establish the effectiveness of SSE for alleviating AIS in terms of reducing Cobb angle, improving trunk asymmetry and quality of life (QoL). Additionally, it aims to define th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 53 publications
0
51
2
1
Order By: Relevance
“…One systematic review of spinal manipulative therapy for Adolescent Idiopathic Scoliosis found only four studies with small sample sizes and concluded there was insufficient evidence to determine efficacy ( Théroux et al, 2017 ). The Scoliosis Research Society (2020) states, “Alternative treatments to prevent curve progression or prevent further curve progression such as chiropractic medicine, physical therapy, and yoga have not demonstrated any scientific value in the treatment of scoliosis.” A recent systematic review concluded that although some scoliosis-specific exercise (SSE) trials have demonstrated improvements in radiographic as well as patient-reported outcomes, overall, there is insufficient evidence to prove that SSE can reduce Cobb angle or improve trunk balance and Quality of Life ( Fan et al, 2020 ). This creates an ethical tension between the biomedicine-trained orthopaedist/nurse and the family who wish to seek CAM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review of spinal manipulative therapy for Adolescent Idiopathic Scoliosis found only four studies with small sample sizes and concluded there was insufficient evidence to determine efficacy ( Théroux et al, 2017 ). The Scoliosis Research Society (2020) states, “Alternative treatments to prevent curve progression or prevent further curve progression such as chiropractic medicine, physical therapy, and yoga have not demonstrated any scientific value in the treatment of scoliosis.” A recent systematic review concluded that although some scoliosis-specific exercise (SSE) trials have demonstrated improvements in radiographic as well as patient-reported outcomes, overall, there is insufficient evidence to prove that SSE can reduce Cobb angle or improve trunk balance and Quality of Life ( Fan et al, 2020 ). This creates an ethical tension between the biomedicine-trained orthopaedist/nurse and the family who wish to seek CAM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The International Scientific Society for Orthopedic and Rehabilitation Treatment of Scoliosis (SOSORT) in 2016 [13] issued a guideline that includes a total of 68 recommendations, which are divided into the following topics: spine fixation, prescriptions for preventing the progression of scoliosis during growth, during treatment with corset and surgical therapy and other conservative methods of treatment (exercises for impaired respiratory function, general sports activities). Some of the authors in their works [6,8] expressed the point of view that such methods of treatment as the Schroth method, physiotherapy, chiropractic and electrical stimulation, massage [5,7] have a dubious positive result in eliminating the progression of scoliotic disease, while others scientists came to the conclusion that the use of a night corset [9], spine fi xation for 23 hours, physiotherapeutic treatment [12], Schroth method [4], combined kinesitherapy with diff erential electrotherapy (TENS-therapy and electromyostimulation) [14] at moderately progressive idiopathic scoliosis (<25°) confi rms the eff ectiveness of non-surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…First, no untreated control group was included for comparison of intervention effects. However, because of the proven benefits of PSSE on AIS [11][12][13], it was unethical to leave participants without treatment for as long as 2 years. Thus, the benefit observed may have been influenced by natural recovery of the condition.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, scoliosis-specific exercise is a nonoperative option that is well received by patients and families [8]. Several systematic reviews and randomized controlled trials have reported the positive effects of physiotherapeutic scoliosis specific exercise (PSSE) on slowing curve progression as well as improving cosmetic and quality of life [9][10][11][12]; however, the relationship of curve location with correction effects has not been clearly discussed in these studies, in which small samples of participants have been recruited and followed up over the short-term [13][14][15]. In particular, one 6-month long randomized control trial (RCT) revealed a significant correlation between thoracic curvature with an imbalanced pelvis (n = 15) and the largest curves after Schroth treatment [13]; one 4-month long RCT demonstrated the greater Cobb reduction was noted in the thoracic region (n = 20) after body awareness exercise [14].…”
Section: Introductionmentioning
confidence: 99%